2006
DOI: 10.1103/physreve.74.050901
|View full text |Cite
|
Sign up to set email alerts
|

Bubble statistics and dynamics in double-stranded DNA

Abstract: The dynamical properties of double-stranded DNA are studied in the framework of the Peyrard-Bishop-Dauxois model using Langevin dynamics. Our simulations are analyzed in terms of two distribution functions describing localized separations ("bubbles") of the double strand. The result that the bubble distributions are more sharply peaked at the active sites than thermodynamically obtained distributions is ascribed to the fact that the bubble lifetimes affect the distributions. Certain base-pair sequences are fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
52
2
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 17 publications
(17 reference statements)
10
52
2
7
Order By: Relevance
“…Similar results were obtained for a number of other viral promoters [24,25]. In particular, it was shown that the large bubbles containing the +1 base pair are also the longest-lived (on average) bubbles [26].…”
Section: Transcription and Bubble Formationsupporting
confidence: 68%
“…Similar results were obtained for a number of other viral promoters [24,25]. In particular, it was shown that the large bubbles containing the +1 base pair are also the longest-lived (on average) bubbles [26].…”
Section: Transcription and Bubble Formationsupporting
confidence: 68%
“…Increasing the field amplitude leads to the increase of opening probability at these sites and helps the opening of others. Without the THz field, the opening probability of P5 promoter at the TATA box is higher than at the TSS [31,43]. The most persistent bubbles are found at the sites that have been pointed out before, see Fig.…”
Section: Bubbles Formationsupporting
confidence: 55%
“…It has potential ability to describe the melting transition and denaturation bubbles of the dsDNA such as those that occur during the initial stage of the transcription process. Some specific correlation with transcription initiation sites has been claimed [22,[28][29][30][31] and debated [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…12,13). However, recently it was argued 14,15,16,17,18 that thermodynamic characterization of the thermal fluctuations may differ from a dynamical characterization, which points to the need for a thorough understanding of the dynamical effects in this highly nonlinear and cooperative material.…”
Section: 321mentioning
confidence: 99%